Parents’ experience in pediatric Tuina treatment program for congenital muscular torticollis in infants and children: qualitative findings from individual interviews - Shu Cheng Chen; Xuan Zhang; Juan Yu; Shuang Lan Lin; Fei Fei Ding; Jia Wen Shou; Ge Ren; Lok Yi Pang; Wing Fai Yeung (BMC Complementary Medicine and Therapies)
Abstract Background Pediatric tuina treatment program is an intervention of traditional Chinese medicine that involves specific manual techniques applied to the bodies of infants and children to promote health and treat conditions such as congenital muscular torticollis (CMT). This study was conducted to understand facilitators, barriers, and influencing factors in the implementation of pediatric tuina treatment program based on parents’ experiences. Methods Semi-structured individual interviews were conducted with parents’ experience in Shandong province, China. Purposive sampling was applied to recruit 13 parents whose children had received a pediatric tuina training program for at least three months to participate voluntarily. Interviews were audio-recorded, transcribed verbatim, and analyzed using template analysis to identify key themes and subthemes. NVivo 12 software was used to facilitate the organization and coding of the data. Results Three themes were identified: (1) facilitators to the use of pediatric tuina treatment program, (2) barriers to the use of pediatric tuina treatment program, and (3) modulating factors of the use of pediatric tuina treatment program. The theme of the facilitators of intervention implementation included the subthemes of (a) merits of pediatric tuina, (b) perceived benefits by patients, and (c) parents’ concerns and expectations. The theme of barriers to intervention implementation included the subthemes of (a) perceived problems by patients, (b) limited medical resources, (c) family pressure, and (d) manipulation particularity. Modulating factors included (a) parents’ perception, (b) patients’ adherence, and (c) parents’ mentality. Conclusion Perceived beneficial effects on improving children’s CMT symptoms and constitutions as well as the conservative nature of pediatric tuina treatment mainly facilitated the treatment. Disease recurrence limited medical resources, long-term family pressure, and noncooperation of children were the dominant barriers to treatment implementation. Parents’ adherence, mentality, and perceptions on CMT and intervention selection modulated the effects of the treatment. Further research is needed to confirm these findings and explore additional factors affecting the effectiveness and implementation of pediatric tuina treatment.